Use of T1-weighted MR imaging to differentiate between primary polydipsia and central diabetes insipidus. - Moses, A M; Clayton, B; Hochhauser, L (American Journal of Neuroradiology, 1992)
PURPOSE To investigate the value of MR in differentiating patients with primary polydipsia, who have an intact neurohypophyseal system, from those with central diabetes insipidus, who have impaired synthesis and/or release of vasopressin.METHODS Eighteen patients with clinically significant hypotonic polyuria were diagnosed endocrinologically as having primary polydipsia or diabetes insipidus (central or nephrogenic). These patients, and 92 patients without sellar disease, were then imaged with 1.5-T, T1-weighted, thin sagittal sections without gadolinium contrast.RESULTS Normal hyperintense signal of the neurohypophysis was present in 90 of 92 patients without sellar disease. The signal was also present in all six patients with primary polydipsia. In contrast, the hyperintense signal was absent in all eight patients with central diabetes insipidus. Three of the four patients with nephrogenic diabetes insipidus also had an absent hyperintense signal.CONCLUSION T1-weighted MR may prove important in differentiating patients with central diabetes insipidus from those with primary polydipsia.